Electromagnetic shielding material, film and preparation method thereof

By introducing interlayer bonding points of A atoms between the MXene sheets, A-MXene materials were prepared, which solved the problem of high resistance of MXene materials, and achieved efficient electromagnetic shielding performance and excellent thermal stability.

CN115991475BActive Publication Date: 2025-02-28BEIHANG UNIV

Patent Information

Application Number
CN202211516447.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-29
Publication Date
2025-02-28
Estimated Expiration
2042-11-29

AI Technical Summary

Technical Problem

MXene materials containing -Cl functional groups have high resistance, which limits their application in the field of electromagnetic shielding.

Method used

Adding the interlayer bonding points or bonding segments of A atoms between the MXene sheets gives a new MXene material (A-MXene), which has excellent stability and low-thin layer resistance characteristics.

Benefits of technology

The A-MXene material significantly reduces the thin layer resistance, improves the electromagnetic shielding performance, exhibits oxidation resistance up to 400°C and a low thin layer resistance of 9.3Ω/□, and reaches 39dB of EMI shielding performance at a low thickness of 3.1μm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115991475B_ABST
    Figure CN115991475B_ABST
Patent Text Reader

Abstract

The present invention discloses an electromagnetic shielding material, a film and a preparation method thereof, wherein the electromagnetic shielding material comprises an A-MXene material, wherein there are bonding points or bonding segments of M-A-M between MXene sheets of the A-MXene material, wherein the A is selected from at least one of elements of group VIIB, VIII, IB, IIB, IIIA, IVA, VA or VIA, and the M represents a transition metal element in the MXene sheet; the preparation method of the electromagnetic shielding material comprises: reacting an initial MXene material with a single substance or compound of A at a predetermined temperature for a predetermined time; the initial MXene material is a MXene material containing a Cl, a Br or an I functional group. The present invention aims at the technical problem that the MXene material containing a Cl functional group has high resistance when applied to the field of electromagnetic shielding, and increases interlayer bonding points or bonding segments of A atoms between MXene sheets to obtain a novel electromagnetic shielding material having both excellent stability and low sheet resistance characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electromagnetic shielding, and in particular relates to an electromagnetic shielding material, a film and a preparation method thereof. Background Art

[0002] The rapid development of integrated electronic devices and the widespread use of telecommunication networks have led to serious electromagnetic interference (EMI), which has adverse effects on the functions of electronic devices and even human health. Therefore, there is an urgent need to explore suitable shielding materials that can effectively absorb or reflect unwanted electromagnetic radiation. According to the Schelkunoff theory, the total EMI shielding effectiveness (SE T ) consists of three parts: (1) reflection attenuation (SE R ), which is caused by impedance mismatch between propagation media; (2) absorption attenuation (SE A ), depends on the conductivity and thickness of the EMI shield; (3) multiple reflection attenuation (SE M ), because the total shielding efficiency >15dB can be ignored. Therefore, highly conductive metals (such as Al, Cu, Ag) have been widely used for EMI shielding. However, these metals usually have high density (2.7 ~ 10.5g cm -3 ) and poor processability make it difficult to use in small mobile electronic devices. Compared with metals, the density is low (0.3-2.6 g cm -3 Carbonaceous materials (carbon nanotubes, graphene) and carbides / nitrides (MXene) have been studied as potential candidates for EMI shielding. In particular, Ti3C2F x MXene films generally exhibit high EMI shielding capabilities (29-92 dB), depending on the film thickness.

[0003] MXene is an atomic layer of carbide, nitride and carbonitride with the general formula M n+1 X n T x (n=1~4), where M is an early transition metal (such as Ti, V, Nb), X is carbon and / or nitrogen, and T is a surface termination (such as -F, -O, -OH, -Cl). The preparation method of MXene materials has a direct impact on the structure, morphology and properties of the obtained MXene materials. At present, the preparation method of MXene materials focuses on how to peel off the precursor MAX phase to obtain a two-dimensional MXene material. These methods are inseparable from the participation of fluoride ions. The earliest reported etching method is HF etching, which can be used to etch MAX phases where most of the A atomic layer is Al. The principle is that the F in HF -Reacting with Al atoms to generate AIF3, the M-Al bond is broken, the Al sublayer is selectively etched away, and the MX layer is not affected. During the etching process, accompanied by the generation and escape of H2, the layered bulk structure of the MAX phase gradually transforms into a fluffy "accordion" structure formed by a large number of two-dimensional MXene sheets stacked by van der Waals forces, that is, multi-layer MXene. The multi-layer MXene obtained by HF etching can weaken its interlayer van der Waals force after intercalation with an intercalating agent, and can be peeled off into a single-layer MXene nanosheet after ultrasonic treatment. The in-situ HF etching method is an improved etching method. A mixture of fluoride-containing salts (LiF, NaF, KF, etc.) and acids (HCl, H2SO4, etc.) is used as an etchant to avoid the direct use of highly corrosive HF. More importantly, the LiF / HC1 etching system in this method can directly peel off the accordion-shaped MXene into a single-layer MXene nanosheet by hand shaking or mild ultrasonic treatment after etching. Since no additional intercalation step is required, the preparation process of MXene nanosheets is greatly simplified, and this method has become the most widely used etching method. However, the MXene materials containing fluorine functional groups (-F) obtained by liquid phase etching usually show extremely poor stability. When MXene is dispersed in water, it will quickly oxidize and degrade to form metal oxides and carbon.

[0004] The applicant's prior patent application (application number: 202011466046.4) also proposed a vapor phase method for preparing MXene, using vapor phase etchants such as halogen hydrides, metal halides, nitrogen hydrides, etc. as etchants to prepare MXene materials with accordion morphology, among which the MXene material terminated with halogen elements -Cl showed good stability. In Ar atmosphere, this Cl-terminated MXene material showed good stability at temperatures up to 750°C without structural degradation, which is in contrast to the poor stability of MXene containing -F functional groups produced by liquid etching. However, these -Cl-terminated MXenes show relatively high resistance (>10 4 Ω / □), which limits the application of this type of MXene materials in the field of electromagnetic shielding. Summary of the invention

[0005] In view of the technical problem of the relatively high resistance of MXene materials containing -Cl functional groups, the present invention provides a new modification path, that is, adding interlayer bonding points or bonding segments of A atoms between MXene sheets to obtain a new type of MXene material (A-MXene) with both A atom bonding force and van der Waals force between MXene sheets. This new type of MXene material has both excellent stability and low sheet resistance characteristics, and this A-MXene material is applied to the field of electromagnetic shielding. Compared with MAX phase materials, the A-MXene nanosheets of the present invention have the two-dimensional morphology and surface functional group characteristics of MXene. Compared with two-dimensional MXene materials, the A-MXene nanosheets have incomplete A atom bonding between the layers. Therefore, the A-MXene nanosheets can be represented by the chemical formula M n+1 A m X n T x , where 1 ≤ n ≤ 4, 0 < m < 1, 0 < x < 2.

[0006] In the first aspect of the present invention, an electromagnetic shielding material is provided. The electromagnetic shielding material includes an A-MXene material. There are bonding points or bonding segments of M-A-M between the MXene sheets of the A-MXene material. A is selected from at least one of the elements in Group VIIB, VIII, IB, IIB, IIIA, IVA, VA or VIA, and M represents a transition metal element in the MXene sheet.

[0007] In some embodiments, the above A-MXene material is represented by the chemical formula M n+1 A m X n T x , where 1 ≤ n ≤ 4, 0 < m < 1, 0 < x < 2; where M is selected from one or more of the transition metal elements.

[0008] In some embodiments, the above A is selected from one or more of the elements such as aluminum, sulfur, cobalt, nickel, gold, silicon, phosphorus, sulfur, iron, manganese, copper, zinc, gallium, germanium, arsenic, cadmium, indium, tin, thallium, lead, bismuth, etc.

[0009] In some embodiments, the above A is selected from at least one of aluminum, indium, tin, gallium, germanium, silicon.

[0010] In some embodiments, the above X is selected from one or more of the elements carbon, nitrogen or boron.

[0011] In some embodiments, the above A-MXene material has an accordion-like or two-dimensional nanosheet morphology.

[0012] A second aspect of the present invention provides a method for preparing the above-mentioned electromagnetic shielding material, comprising the steps of: reacting an initial MXene material with a single substance of A or a compound of A at a predetermined temperature for a predetermined time; the initial MXene material is a MXene material containing -Cl, -Br or -I functional groups.

[0013] In some embodiments, the preparation method further includes a stripping step, in which the A-MXene material with an accordion morphology obtained by the reaction is ultrasonically or mechanically stripped to obtain an A-MXene material with a two-dimensional structure.

[0014] In some embodiments, the method for preparing the initial MXene material comprises: etching component A in the MAX phase material using a molten salt method or a gas phase method.

[0015] In some embodiments, the molten salt method uses a halogen metal salt as an etchant; preferably, a chloride metal salt is used.

[0016] In some embodiments, the gas phase method uses one or more of hydrogen halide gas, halogen element gas, and sublimated halogen metal salt gas as an etchant.

[0017] In some embodiments, the predetermined temperature is between 700°C and 1200°C; preferably, the predetermined temperature is between 700°C and 900°C.

[0018] In some embodiments, the predetermined time is between 0.01 min and 12 h.

[0019] In some embodiments, A is metal aluminum powder, and the reaction time is ≤5 min; or, A is metal silicon powder, and the reaction time is ≤4 h; or, A is metal gallium powder, and the reaction time is ≤5 h; or, A is metal germanium powder, and the reaction time is ≤5 h; or, A is metal indium powder, and the reaction time is ≤1 h; or, A is metal tin powder, and the reaction time is ≤4 h; or, A is metal zinc powder, and the reaction time is ≤2 h.

[0020] A third aspect of the present invention provides an electromagnetic shielding film, which contains the electromagnetic shielding material described above; or, the electromagnetic shielding material obtained by the above preparation method.

[0021] A fourth aspect of the present invention provides a method for preparing the above-mentioned electromagnetic shielding film, the steps comprising: preparing the above-mentioned A-MXene material and a solvent into a dispersion liquid, and forming a thin film layer on a substrate by spraying, filtering or coating.

[0022] A fifth aspect of the present invention provides an electromagnetic shielding coating, wherein the coating contains the electromagnetic shielding material described above; or, the electromagnetic shielding material obtained by the above preparation method.

[0023] The beneficial technical effects of the present invention are:

[0024] (1) The elemental composition, morphology, structure, and types of surface functional groups of MXene materials have a direct impact on their performance. Further modification of MXene materials can expand the family of MXene materials and endow MXene materials with unique and novel physical or chemical properties. Existing modification methods of MXene materials usually focus on adjusting the constituent elements of MXene or its surface functional groups, or adjusting the etching environment by selecting different etchants to obtain MXene materials with different sheet diameters or thicknesses. The present invention provides a new modification design direction for MXene materials, namely, adding interlayer bonding points or bonding segments of A atoms between MXene sheets to obtain a new type of MXene material with both A-atom bonding force and van der Waals force between MXene sheets. In order to distinguish the two-dimensional MXene or accordion-shaped MXene materials in the prior art, the new type of MXene material with interlayer A-atom bonding obtained by the present invention is labeled as A-MXene.

[0025] (2) The present invention prepares a new electromagnetic shielding material (A-MXene material) with excellent thermal stability and electrical conductivity. The A-MXene material can be used to construct a large-area continuous aggregate (such as a film). x Thin film tests showed good oxidation resistance up to 400°C and low sheet resistance of 9.3Ω / □, significantly lower than Ti3C2Cl x Film (4.0×10 4 Ω / □).

[0026] (3) The A-MXene film of the present invention has a layer-by-layer stacked multi-interface structure and low sheet resistance, providing many interfaces for the incident electromagnetic wave (EM) to undergo internal reflection, which will enhance the interaction probability between EM and electric dipoles, thereby increasing the absorption loss; the Al-Ti3C2Cl x The film shows excellent electromagnetic shielding performance and exhibits good EMI shielding performance at a low thickness of 3.1μm with a total SE value of 39dB. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 . Al-Ti3C2Cl obtained in a specific embodiment of the present invention x (A-MXene) and Ti3C2Cl x Optical comparison photo of (initial MXene) shows that Al-Ti3C2Cl x It is gray-black, while Ti3C2Cl x is black.

[0028] Figure 2 In one embodiment of the present invention, a) the initial MXene (Ti3C2Cl x ) to the interlayer with bonding A-MXene (Al-Ti3C2Cl x ) Schematic diagram of the atomic structure change; b) Initial MXene (Ti3C2Cl x ) shows the accordion-shaped structure; c) the initial MXene (Ti3C2Cl x ) and d) magnified HAADF images showing Ti3C2Cl x The MXene layers in the image are arranged in an orderly manner, and the inset in c) corresponds to the FFT pattern; e) A-MXene (Al-Ti3C2Cl x ) shows that it retains the accordion morphology of the initial MXene; f) A-MXene (Al-Ti3C2Cl x ) and g) magnified HAADF images showing the presence of a single Al atomic layer pinned to the adjacent Ti3C2Cl x Between MXene sheets; in d) and g) atomic structure schematics, Ti, Cl, and Al atoms are represented by red, blue, and yellow balls, respectively.

[0029] Figure 3 . In one embodiment of the present invention a and b) initial Ti3C2Cl x TEM images of the cross section at different magnifications; c and d) are Al-Ti3C2Cl x TEM images of the cross section at different magnifications.

[0030] Figure 4 . In one embodiment of the present invention a) Al-Ti3C2Cl x and b) Ti3C2Cl x HAADF image of .

[0031] Figure 5 .a) and b) are Al-Ti3C2Cl in one embodiment of the present invention x In the reaction time of 0 to 5min, the in situ XRD spectrum of the product is shown in Ti3C2Cl x A new peak is shown at 9.2° near the (002) peak of MXene. The peak marked by the black triangle belongs to aluminum powder. c) and d) are XRD spectra of A-MXene with different A atoms bonded between layers obtained by using different A element powders as reactants in other embodiments of the present invention, which are similar to Al-Ti3C2Cl xSimilarly, all the A-MXenes produced by the reactions have the same x A new peak adjacent to the (002) peak.

[0032] Figure 6 . In one embodiment of the present invention a) Al-Ti3C2Cl x SEM image showing the accordion-like morphology; b) Al-Ti3C2Cl x The XRD pattern of the film shows an obvious peak at 9.2°; c) Al-Ti3C2Cl x Cross-sectional SEM and d) magnified image of the film; e) Al-Ti3C2Cl x HRTEM of nanosheets and Al-Ti3C2Cl x The corresponding FFT (inset) image of the MXene layer shows the single-crystalline characteristics. f) Al-Ti3C2Cl x The EDS spectra of the films show the uniform distribution of Ti, Al, Cl and C species.

[0033] Figure 7 . In one embodiment of the present invention a) Al-Ti3C2Cl x TEM and b) HRTEM images of the nanosheets, showing the thin-layer characteristics and good hexagonal arrangement of Ti atoms. cf) EDS mapping images showing the uniform distribution of c) Ti, d) Al, e) Cl, and f) C.

[0034] Figure 8 . Al-Ti3C2Cl in one embodiment of the present invention x SEM images of the cross section of the film at different magnifications. The film consists of Al-Ti3C2Cl with a lateral size of hundreds of nanometers. x The nanosheets are densely stacked.

[0035] Fig. 9 . Al-Ti3C2Cl assembled in one embodiment of the present invention x Film properties and EMI shielding performance. a) Ti3C2Cl x and Al-Ti3C2Cl x TG curves of the films. The inset in a shows the Al-Ti3C2Cl x The film is gray, while Ti3C2Cl x The film is blue, and the scale bar is 0.5 cm; b) The IV curve of the film shows that Al-Ti3C2Cl x The film has a higher x Much lower sheet resistance of the film; c) Al-Ti3C2Cl xSchematic diagram of multiple reflections and absorption in the film. The orange, green, black, blue and gray arrows represent the incident, reflected, multiple reflected, absorbed and transmitted electromagnetic waves, respectively; d) EMI shielding diagram shows that Al-Ti3C2Cl x The film has a higher x Thin film with larger SE T Value; e)Al-Ti3C2Cl x EMI SET images of the films show enhanced performance with increasing thickness; f) Al-Ti3C2Cl with increasing thickness x EMI SE of thin films T , SE R and SE A value. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is described below by specific embodiments. It should be understood that one or more steps mentioned in the present invention do not exclude the existence of other methods and steps before and after the combination step, or other methods and steps can be inserted between these explicitly mentioned steps. It should also be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Unless otherwise specified, the numbering of each method step is only for the purpose of identifying each method step, and does not limit the order of arrangement of each method or limit the scope of implementation of the present invention. The change or adjustment of the relative relationship thereof can also be regarded as the scope of implementation of the present invention without substantial changes in the technical content.

[0037] The chemicals used in the embodiments of the present invention and their specifications and manufacturers are as follows:

[0038] Ti (99.99%, 300 mesh, Innochem), Al (99.95%, 25 μm, Aladdin reagent), graphite (99.9%, 10 mesh, Alfa Aesar), Si (99.999%, 325 mesh, Innochem), Ga (99.995%, Innohem), Ge (99.999%, 200 mesh, Innothem), In (99.99%, Innochem), Sn (99.99%, 325 mesh, Innochen), CdCl2 (99.996%, ultra dry, Alfa-Aesar), N,N-dimethylformamide (DMF, 99.9%, Beijing reagent), HCl (35%-37%, Beijing reagent). All reagents were used directly without further purification.

[0039] In the embodiment of the present invention, the crystal structure, morphology and microstructure of the sample are characterized by an X-ray diffractometer (Rigaku D / MAX2200pc, Cu Kα radiation with energy of 8.0keV), a field emission scanning electron microscope (ZEISS, GeminiSEM 500), an X-ray diffraction analyzer (XRD), an X-ray diffractometer (XRD, XRD), a transmission electron microscope (JEOL, JEM-2100F) and a spherical aberration corrected transmission electron microscopy (FEITitan G2). Thermogravimetric-differential scanning calorimetry (TG-DSC) curves are obtained on a thermogravimetric analyzer (NETZSCH STA449F5 / F3 Jupiter). The EMI shielding performance in the range of 8.2-12.4GHz is measured by a Keysight N5224B PNA vector network analyzer. The sheet resistance is measured using a 4-point probe (MCP-TP06P PSP) and a Loresta GP instrument (MCP-T610 model, Mitsubishi Chemical, Japan).

[0040] The preparation steps of TEM samples include: firstly, the obtained Al-Ti3C2Cl x MXene nanosheets were dispersed in 2 mL of ethanol solvent and then ultrasonicated for 15 min. After 5 min of storage, the diluted dispersion was dropped onto a holey carbon grid (200 mesh) to obtain a TEM sample.

[0041] The raw materials and instruments used in the examples are not specified, and there is no particular limitation on their sources. They can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0042] The preparation steps of the initial MXene in this embodiment include: (1) etching the MAX phase material by a molten salt method or a gas phase method to obtain an accordion-shaped MXene; (2) exfoliating the accordion-shaped MXene to obtain a two-dimensional MXene nanosheet. The specific preparation process is as follows:

[0043] The MAX phase material used in this embodiment is synthesized by high temperature sintering method, and the specific steps include: sealing titanium powder (Ti), aluminum powder (Al) and graphite powder (C) with a molar ratio of 3:1.3:1 in an agate container, and grinding the powder mixture at 600rpm for 20 hours. Then, the powder is heated to 1400℃ in a tube furnace and maintained at this temperature for 4 hours under an argon environment. After cooling to room temperature, the block is ground into powder and washed with HCl solution to remove residual Al powder, and then washed with water vacuum filtration until pH=7, and vacuum dried to obtain MAX phase Ti3AlC2.

[0044] The Cl-terminated MXene in this embodiment can be prepared by a molten salt method or a gas phase method. Specifically, the molten salt method includes: grinding the above-obtained MAX phase (0.5 g) and CdCl2 / CdBr2 (molar ratio 1:8) powder in a mortar for 5 minutes to mix the powders evenly; placing the above-mentioned powder mixture in a tube furnace in an argon environment and heating it to 610°C at 10°C / min and keeping it at 610°C for 6 hours, and naturally cooling it to room temperature; taking out the cooled product and dissolving it with deionized water, then adding hydrochloric acid solution to remove Cd and filtering it, freeze-drying the filtered product to obtain an accordion-Cl-terminated MXene (accordion-shaped Ti3C2Cl x The gas phase method comprises the following steps: placing the MAX phase obtained above in a high temperature tube furnace, heating it to 700°C-800°C at 10°C / min under an argon atmosphere, then introducing HCl gas into the tube furnace, keeping the temperature for 30 minutes, and then naturally cooling it to room temperature to obtain accordion-shaped Cl-terminated MXene (accordion-shaped Ti3C2Cl x ).

[0045] The accordion-shaped Cl-terminated MXene prepared by the above-mentioned melting method or gas phase method was exfoliated by ball milling to obtain two-dimensional MXene nanosheets (two-dimensional Ti3C2Cl x ), the specific steps include: 500mg accordion-shaped Ti3C2Cl x The powder was evenly dispersed in 20 mL of N,N-dimethylformamide (DMF) solution. Then, the solution was ball-milled at 300 rpm for 8 hours; the obtained liquid was ultrasonically treated for 30 minutes, and then centrifuged at 2000 rpm and 8000 rpm for 15 minutes to obtain two-dimensional MXene nanosheets (two-dimensional Ti3C2Cl x ).

[0046] This embodiment provides a Ti3C2Cl x MXene, labeled A-Ti3C2Cl x , where A is Al, Sn, In, Ge, Ga, and Si respectively. The two-dimensional Ti3C2Cl prepared and exfoliated by the above molten salt method x As raw material MXene. The preparation steps include:

[0047] The two-dimensional Ti3C2Cl xand a single substance powder of A. In order to avoid oxidation, all preparation processes are carried out in a glove box filled with argon with an oxygen and moisture content of less than 0.1 ppm. After mixing, the mixture sample is placed in a high-temperature tube furnace and heated under an argon atmosphere and maintained at a predetermined reaction temperature for a predetermined reaction time. After naturally cooling to room temperature, it is taken out, and the A component is removed by acid washing, and then dried.

[0048] In this embodiment, the single powders of A are: aluminum powder (Al), tin powder (Sn), indium powder (In), germanium powder (Ge), gallium powder (Ga), silicon powder (Si). Please see Table 1 for the specific ratio, reaction temperature and reaction time:

[0049] Table 1. Ti3C2Cl with interlayer A atoms bonded x Reaction conditions of MXene

[0050]

[0051] To prepare interlayer Al-bonded Ti3C2Cl x MXene(Al-Ti3C2Cl x ) is used as an example to illustrate the reaction mechanism of the preparation process. During the reaction, since the bonding energy of Al-Cl (507±1.0kJ / mol) is higher than that of Ti-Cl (405.4±10.5kJ / mol), metal Al will react with the two-dimensional Ti3C2Cl x The Cl terminal of MXene reacts to form gaseous aluminum chloride (AlCl3, sublimation temperature 180°C). The byproduct gaseous aluminum chloride can be easily removed from the reaction system. At the same time, the additional metal Al will react with the exposed Ti atoms and connect the two-dimensional Ti3C2Cl x Adjacent layers of MXene generate interlayer Al-bonded Ti3C2Cl x MXene. After the reaction, black MXene powder (Ti3C2Cl x ) will turn into gray-black powder (Al-Ti3C2Cl x )(See Figure 1 ).

[0052] Table 2 gives the melting points and boiling points of the above-mentioned A element and A chlorides. It can be seen that not only AlCl3 but also other A chlorides have lower boiling points and can be easily removed from the reaction system.

[0053] Table 2. Melting point and boiling point values ​​of A element and A chloride in this example

[0054]

[0055]

[0056] We performed transmission electron microscopy (TEM) and high-resolution TEM (HRTEM) tests on Al-Ti3C2Cl x With Ti3C2Cl x As an example, the morphology and structure of the two are compared to illustrate the morphology and structural characteristics of the A-MXene of the present invention. Figure 2 As shown, Figure 2 a shows the initial MXene (Ti3C2Cl x ) is transformed into A-MXene (Al-Ti3C2Cl x ) shows the atomic structure transformation diagram. It can be seen that during the reaction, Ti3C2Cl x The Cl functional groups (blue balls) on the surface are released, resulting in the exposure of Ti atoms (red balls). The exposed Ti atoms are bonded to Al atoms (yellow balls). The exposed Ti atoms in adjacent layers are bonded to each other through Al atoms, forming a new MXene material with interlayer Al atoms (Al-Ti3C2Cl x ). Figure 2 b and c give Ti3C2Cl x and Al-Ti3C2Cl x From the cross-sectional TEM image, we can see that Al-Ti3C2Cl x Retained Ti3C2Cl x The morphology of the thin strips is characterized by a width ranging from a few nanometers to tens of nanometers; but it is different from Ti3C2Cl x Compared with Al-Ti3C2Cl x The adjacent stripes become closer and straighter (see Figure 3 ).

[0057] Atomic resolution high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) images show ( Figure 2 f), in the marked part, Al-Ti3C2Cl x There is a clear fixed single atom between two adjacent sheets in Ti3C2Cl x The MXene sheets are terminated by Cl, and these fixed single atoms are Figure 2 c for Ti3C2Cl x It is not visible in the characterization of Al-Ti3C2Cl x A magnified atomic image of Figure 2 g) clearly shows that two adjacent layers are connected by a dark atomic layer and composed of three bright atomic layers. In STEM images, the brightness of an atom is proportional to the square of its atomic number. Therefore, Al-Ti3C2Cl xThe dark layer and the bright layer are Al layer and Ti layer respectively; Figure 2 g also gives a schematic diagram of the atomic arrangement model, where the yellow balls are Al atoms, the red balls are Ti atoms, and the blue balls are Cl atoms; Al-Ti3C2Cl x The interlayer spacing of is much lower than Figure 2 In d, Ti3C2Cl x the interlayer distance of the layer is close to the interlayer spacing of the Ti3AlC2 MAX phase This contraction of the interlayer spacing should be driven by the appropriate crystal symmetry of the MAX phase. Unexpectedly, on the outermost layer of the Al-Ti3C2Cl x MXene sheets, that is, on the outermost Ti atoms, there are still small and bright atomic arrangements, and these arranged atoms should be Cl terminal functional groups. This indicates that Al atoms can bond to adjacent Ti3C2Cl x MXene sheets, rather than replacing the outermost Cl terminal functional groups. Therefore, a novel MXene material (A-MXene) with partial A bonding between layers and having a unique heterostructure is obtained in the present invention.

[0058] Compared with the MAX phase material, the A-MXene material of the present invention has incomplete A atomic bonding between layers. Therefore, the A-MXene material can be represented by the chemical formula M n+1 A m X n T x , where 1 ≤ n ≤ 4, 0 < m < 1, 0 < x < 2; for example, Al-Ti3C2Cl in the examples x , can also be represented as Ti3Al m C2Cl x .

[0059] Figure 4 a and b further give the HAADF images of Al-Ti3C2Cl x and Ti3C2Cl x at another magnification. By comparison, it can be clearly seen that there are single-layer Al atomic bonding segments between the MXene sheets in Al-Ti3C2Cl x , and there are bonding forces and van der Waals forces between Al and Ti in the interlayer of Al-Ti3C2Cl x ; while these bonding segments do not exist in Ti3C2Cl x , the outermost layer of the MXene sheets is the Cl-capped functional group, and the main force between the MXene sheets is the van der Waals force.

[0060] In order to further understand the reaction process, we performed in situ X-ray diffraction (XRD) measurements during the reaction. Figure 5 As shown, the initial MXene (Ti3C2Cl x ) and aluminum powder (Al) showed a series of characteristic peaks at 7.9°, 15.9°, 24.0°, 57.8° and 38.4°, 44.6°, 65.0°, corresponding to the initial MXene (Ti3C2Cl x )'s (002), (004), (006), (110) crystal planes and Al metal's (111), (200), (220) crystal planes (marked with black inverted triangles) ( Figure 5 pristine curve in a); as the reaction proceeds, from 0 to 5 min, it can be observed that the intensity of the three characteristic peaks of Al metal gradually decreases and disappears after 3 min; at the same time, the initial MXene (Ti3C2Cl x )'s (002) continuously widens to a higher degree, indicating that the interlayer spacing shrinks; after 5 min, the shrinkage stops, which is related to the appearance of a new characteristic peak at 9.2°, which points to Al-Ti3C2Cl x The new characteristic peak corresponds to a higher value than the initial MXene (Ti3C2Cl x )(7.9°), close to the Ti3AlC2 MAX phase (9.4°). The calculated value of the characteristic peak corresponds to the (002) interplanar spacing of This is consistent with the above HAADF-STEM image ( Figure 2 g) is very consistent with the observation results. In addition, another characteristic peak appears at 38.8°, which is higher than that of the initial MXene (Ti3C2Cl x )(38.4°) is much stronger and higher, close to the (104) plane of Ti3AlC2 MAX phase (39.0°), which should originate from Al-Ti3C2Cl x The crystal symmetry of the Ti3AlC2 MAX phase present in the x and Ti3C2Cl x Except for the peak of , no obvious impurity peak (such as Ti-Al alloy) was detected, indicating that Al only participated in the bonding reaction.

[0061] It is worth noting that white smoke appeared in the reaction tube furnace within 3 minutes. After being collected, the white smoke was characterized by XRD test to be AlCl3, indicating that the A-MXene (Al-Ti3C2Cl x) should begin to form within 3 minutes, indicating a fast reaction speed, which also reveals that this interlayer bonding reaction is thermodynamically feasible and has fast kinetic characteristics. According to this principle, other A component elements should also undergo bonding reactions with MXene. In other embodiments of the present invention, different A components are replaced (see Table 1), and different A-MXene materials are obtained by high-temperature reactions in the range of 800°C to 900°C, namely Si-Ti3C2Cl x 、Ga-Ti3C2Cl x 、Ge-Ti3C2Cl x 、In-Ti3C2Cl x 、Sn-Ti3C2Cl x The XRD patterns of these A-MXene materials are as follows: Figure 5 As shown in c and d, it can be seen that these A-MXene materials are similar to the above-mentioned Al-Ti3C2Cl x Similarly, a new peak appears adjacent to the (002) peak of MXene (see Figure 5 b and d), which proves that the MXene material (A-MXene) with corresponding interlayer A atoms bonded is successfully synthesized. The A-MXene material also has an accordion-like morphology, which can be observed by scanning electron microscopy (SEM). By testing the element distribution, it can be seen that Ti, Cl and the corresponding A element are evenly distributed in the material. It is particularly noteworthy that when Ti3C2Cl x When reacting with Si or Ge powder, Si and Ge powder are solid at the reaction temperature (see Table 2), which indicates that solid diffusion reaction is also feasible for the bonding reaction of the present invention. Based on this finding, more A components (such as sulfur, cobalt, nickel, gold, phosphorus, sulfur, iron, manganese, copper, zinc, arsenic, cadmium, tin, thallium, lead, bismuth, etc.) can be induced to react with MXene through the bonding reaction of the present invention to obtain A-MXene materials with A bonding between layers.

[0062] Since the prepared A-MXene has an accordion-like structure, A-MXene nanosheets can be obtained after peeling it off. Through the interaction between the nanosheet layers, it can be easily assembled to obtain an aggregate material (such as a film or sheet material) composed of A-MXene nanosheets with a lateral size of several microns or tens of microns (such as a lateral size of 0.1 microns to 100 microns). One embodiment of the present invention also provides a film assembled from A-MXene materials and a preparation method thereof, the steps comprising: dispersing the A-MXene material prepared by the present invention in a solution, ultrasonically peeling it into A-MXene nanosheets, and filtering it in a porous membrane to obtain; in a specific embodiment, the steps comprise: mixing the Al-Ti3C2Cl xDispersed in N-methylformamide (NMF) solution to prepare a 5 mg / ml dispersion, ultrasonically dispersed for 4 h, during the ultrasonic process, accordion-shaped Al-Ti3C2Cl x , peeling to form Al-Ti3C2Cl x Nanosheets; spray the ultrasonic dispersion onto the porous membrane, and then dry the thin film on the porous membrane to obtain Al-Ti3C2Cl x The thickness of the film can be easily controlled by the spraying amount. x Replaced with MXene material Ti3C2Cl x Assembled Ti3C2Cl x The film was used as a control sample. Figure 6 a shows the Al-Ti3C2Cl prepared by the present invention x The SEM photo shows that it has an obvious accordion-like morphology, the lateral size of the flakes is about 15-20 μm, and the thickness is about 10 μm. After peeling, Al-Ti3C2Cl x Nanosheets; Figure 6 b shows Al-Ti3C2Cl x Thin film and Ti3C2Cl x Comparison of the XRD spectra of the films shows that Al-Ti3C2Cl x The film material has an obvious peak at 9.2°; Figure 6 e HRTEM and Al-Ti3C2Cl x The corresponding FFT image (inset) of the MXene layer shows single-crystalline features with an average lattice distance of 0.26 nm pointing to the (100) plane. x The Ti atoms in the nanosheets are regularly arranged with hexagonal symmetry, which is also confirmed by the corresponding FFT pattern with hexagonal diffraction spots (inset, Figure 6 e), which is the same as the reported MXenes. Figure 6 c and d show the Al-Ti3C2Cl x The cross-sectional SEM image of the film shows that the Al-Ti3C2Cl x The film is densely assembled from small flakes with a thickness of about 13 μm; Ti and Al elements are evenly distributed in the film layer ( Figure 6 f).

[0063] Figure 7 a and b show Al-Ti3C2Cl x TEM and HRTEM images of nanosheets show a two-dimensional layer structure and good crystal structure; Figure 7 c~f are Al-Ti3C2Clx EDS mapping image of the nanosheets, showing the uniform distribution of Ti, Al, Cl, and C. Figure 8 a~c are Al-Ti3C2Cl with a thickness of about 100 μm prepared in another embodiment of the present invention. x Cross-sectional SEM images of the film at different magnifications.

[0064] In order to verify the electrical conductivity and thermal stability of the material of the present invention, the Al-Ti3C2Cl x The film was subjected to thermogravimetric analysis (TG) and sheet resistance measurement in air atmosphere. The TG results are shown as follows: Fig. 9 As shown in a, Al-Ti3C2Cl x The oxidation process of the film can be divided into two stages: (1) In the temperature range of 30℃ to 400℃, Al-Ti3C2Cl x The film remained stable with no significant weight gain; (2) In the temperature range of 400°C to 800°C, the film gradually oxidized and its weight increased by 8%. x The film was oxidized at a low temperature of 280°C and completely oxidized at 510°C. x The film has a higher x The better oxidation resistance of the films, with higher oxidation temperatures and lower oxidation rates, can be attributed to the in-situ formed Ti and Al oxides, which, as expected, prevent oxygen from invading the inner film, thus showing a better oxidation resistance. More specifically, the sheet resistance measurements ( Fig. 9 b) shows that Al-Ti3C2Cl x The film has a low sheet resistance (9.3Ω / □), which is significantly lower than that of Ti3C2Cl x Film (4.0×10 4 This conductivity enhancement effect can be attributed to the presence of Ti-Al-Ti bonds that connect the individual sheets together.

[0065] Based on the relatively high conductivity and good oxidation resistance of the A-MXene film, we provide an application of the interlayer bonded A-MXene material in the field of electromagnetic shielding. In one embodiment, the Al-Ti3C2Cl x The film is used as an electromagnetic shielding film, that is, the Al-Ti3C2Cl x The electromagnetic shielding effect of the film in the X-band (8.2-12.4GHz), such as Fig. 9 As shown in d, the thickness of Al-Ti3C2Cl is 2.3 μm. xThe total SE value of the film is 31.5 dB, while the comparison sample Ti3C2Cl x The film shows almost zero EMI shielding effect, close to the value of bare mica substrate. To enhance the shielding performance, we increase or decrease the Al-Ti3C2Cl x The amount of nanosheets was adjusted by Al-Ti3C2Cl x The thickness of the film was measured and the Al-Ti3C2Cl x The electromagnetic shielding effect of the film, such as Fig. 9 As shown in e and f, when Al-Ti3C2Cl x When the film thickness is 1.8μm, 2.3μm and 3.1μm, EMI SE T The values ​​are as high as 28.8dB, 32.5dB and 39dB. These values ​​are comparable to those of Ti3C2T produced by HF x The values ​​of the films are comparable (see Table 3). This enhancement of electromagnetic shielding effect with increasing thickness is similar to that of Al-Ti3C2Cl x The increase in the number of interfaces in the film is related to the increase in conductivity. Fig. 9 As shown in c, due to the layer-by-layer stacking structure, Al-Ti3C2Cl x The thin film provides many interfaces for the incident electromagnetic (EM) wave to undergo internal reflection, which will enhance the interaction probability between EM and electric dipoles, thereby increasing the absorption loss. T , SE R and SE A This is demonstrated by the change in absolute values, e.g. Fig. 9 f. SE A The value increases rapidly with the increase of thickness (ΔSE A =8.4dB), and SE R The value is stable and almost independent of film thickness (ΔSE R =1.7dB). Therefore, it can be concluded that the EMI shielding enhancement mainly originates from the improved absorption capacity of the film due to the increase in multi-layer reflection and EM wave absorption.

[0066] Since the enhancement of EMI shielding effect mainly comes from the multi-interface and good conductivity characteristics brought by the structural characteristics of A-MXene, it can be expected that other different types of A-MXene materials can also produce similar technical effects. When A-MXene materials are used for electromagnetic shielding purposes, they can be added to coatings as functional additives to obtain protective coatings with electromagnetic shielding effects. For example, coatings containing A-MXene materials are applied to electronic device substrates to form electromagnetic shielding layers; for example, A-MXene materials are formulated into dispersions and sprayed or applied to the surface of objects to form electromagnetic shielding layers; for example: A-MXene materials are formulated into dispersions with water as the solvent and sprayed on the surface of fabrics to obtain fabrics with electromagnetic shielding effects.

[0067] Table 3. Al-Ti3C2Cl of the present invention x Thin films and Ti3C2T prepared by different methods x Comparison of electromagnetic shielding performance of thin films

[0068]

[0069] The data sources are as follows:

[0070] (1)J.Liu,HBZhang,R.Sun,Y.Liu,Z.Liu,A.Zhou,ZZYu,Adv.Mater.2017,29,1702367.

[0071] (2)A.Iqbal,F.Shahzad,K.Hantanasirisakul,MKKim,J.Kwon,J.Hong,H.Kim,D.Kim,Y.Gogotsi,CMKoo,Science 2020,369,446.

[0072] (3) J.Lipton, J.A. V.Dang,A.Goad,K.Maleski,F.Lavini,M.Han,EHRTsai,GMWeng,J.Kong,E.Riedo,Y.Gogotsi,ADTaylor,Matter 2020,3,546.

[0073] (4)M. Han, X. Yin, K. Hantanasirisakul,

[0074] (5)R.Liu,M.Miao,Y.Li,J.Zhang,S.Cao,X.Feng,ACS Appl.Mater.Interfaces2018,10,44787.

[0075] It should be noted that, since the -Br or -I terminated MXene material has similar properties and similar technical problems (low electrical conductivity) as the -Cl terminated MXene material, in other embodiments, the -Cl terminated MXene (initial MXene) in the embodiment of the present invention is replaced with a -Br or -I terminated MXene material, and the same bonding reaction can also occur by optimizing the reaction conditions to obtain a new A-MXene material containing a -Br or -I functional group. That is, the initial MXene of the present invention includes -Cl, -Br, and -I terminated MXene, preferably -Cl terminated MXene.

[0076] In one embodiment, the MXene (initial MXene, Ti3C2I x ) reacts with zinc powder to obtain Zn-Ti3C2I x , Zn powder and the obtained MXene material-Ti3C2I x The reaction was carried out in a tube furnace at a molar ratio of 1:10, heated to 700 degrees under the protection of argon, kept warm for 2 hours, and cooled naturally to room temperature after the reaction was completed to obtain the product Zn-Ti3C2I x Materials. The initial MXene Ti3C2I x It is obtained by etching Al in MAX phase Ti3AlC2 using iodine vapor as etchant by gas phase method.

[0077] It should be noted that the above embodiment shows an implementation method of obtaining A-MXene by reacting the initial MXene with the single substance powder of A. Since the bonding reaction mechanism of the present invention is that the A atom is bonded to the M atom, in other embodiments, it can also be obtained by reacting the initial MXene with a compound that can react to generate A, for example, these compounds can be hydrides of A, amides of A, and other compounds that can react to generate A, all of which are within the technical concept of the present invention. This is explained below through specific examples.

[0078] In one embodiment, the initial MXene (Ti3C2Cl x ) and AlH3 at 800℃ for 1h to synthesize Al-Ti3C2Cl x .

[0079] In another specific embodiment, SiO2, coke and the initial MXene material (Ti3C2Cl x ) in a molar ratio of 1:5:10 in a tube furnace for reaction, heated to 1200 degrees under the protection of argon, kept warm for 5 hours, and cooled naturally to room temperature after the reaction was completed to obtain the product Si-Ti3C2Cl x During the high temperature sintering process, a reduction reaction occurs: SiO2+2C=Si+2CO, and the generated Si reacts with Ti3C2T x Further reaction occurs to obtain Si-Ti3C2Cl x .

[0080] In another embodiment, SiHCl3 and the initial MXene material are placed in a tube furnace at a molar ratio of 1:10 for reaction, and a mixture of hydrogen and argon is continuously introduced, wherein the volume percentage of hydrogen is 10%, and the mixture is heated to 1000 degrees for 5 hours. After the reaction is completed, the mixture is naturally cooled to room temperature to obtain the product Si-Ti3C2Cl x During the high-temperature sintering process, a reduction reaction SiHCl3+H2=Si+3HCl occurs, and the generated Si reacts with Ti3C2T x Further reaction occurs to obtain Si-Ti3C2Cl x In other embodiments, SiHCl3 may also be replaced by other silicon source compounds, such as SiH4, SiH2Cl2, SiHCl3, Si(CH2CH3)4, etc.

[0081] It should be noted that the present invention provides an A-MXene film and a preparation method thereof, but the A-MXene material of the present invention can also be processed into a profile of a desired shape according to actual needs, such as adding the powder of the A-MXene material into a mold and pressing it into shape.

[0082] It should be noted that the accordion-shaped A-MXene can also be exfoliated into A-MXene nanosheets by other methods, such as mechanical exfoliation methods such as ball milling and crushing.

[0083] In summary, in this invention we provide a new modification approach for MXene materials, through the topological reaction of Cl-terminated MXene and selected A elements at high temperature (700-900℃) to synthesize unique interlayer A-bonded A-MXene materials. During the reaction, MAM bonding is gradually formed between adjacent MXene layers, which is related to the crystal symmetry of the MAX phase and the removal of Cl-terminants by gaseous byproducts. The exfoliated accordion-shaped A-MXene materials can be further converted into A-MXene nanosheets (such as Al-Ti3C2Cl x ), can be used to construct a large-area continuous film. The Al-Ti3C2Cl x The film showed good oxidation resistance up to 400 °C and a low sheet resistance of 9.3 Ω / □, which is significantly lower than that of Ti3C2Cl x Film (4.0×10 4 Ω / □), which benefits from the multi-interface structure and low sheet resistance. The obtained film shows good EMI shielding performance at a low thickness of 3.1μm, with a total SE value of 39dB.

[0084] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. An electromagnetic shielding material, characterized in that: The electromagnetic shielding material includes an A-MXene material, wherein there are MAM bonding points or bonding segments between MXene layers of the A-MXene material, the A is selected from at least one of group VIIB, VIII, IB, IIB, IIIA, IVA, VA or VIA elements, and the M represents a transition metal element in the MXene layer; the A-MXene material contains -Cl, -Br or -I functional groups; and the A-MXene material has incomplete A atom bonding between layers.

2. The electromagnetic shielding material according to claim 1, characterized in that: The A-MXene material is represented by the chemical formula M n+1 A m X n T x , where 1 ≤ n ≤ 4, 0 < m < 1, 0 < x < 2; among them, M is selected from one or more of transition metal elements; and / or, A is selected from one or more of aluminum, sulfur, cobalt, nickel, gold, silicon, phosphorus, sulfur, iron, manganese, copper, zinc, gallium, germanium, arsenic, cadmium, indium, tin, thallium, lead, and bismuth; and / or, X is selected from one or more of carbon, nitrogen or boron; And / or, T is selected from one or more of Cl, Br, and I elements.

3. The electromagnetic shielding material according to claim 2, characterized in that: The A is selected from at least one of aluminum, indium, tin, gallium, germanium, and silicon.

4. The electromagnetic shielding material according to claim 1, characterized in that The A-MXene material has an accordion-like or two-dimensional nanosheet morphology.

5. A method for preparing an electromagnetic shielding material according to any one of claims 1 to 4, characterized in that the steps include: reacting the initial MXene material with a simple substance of A or a compound of A at a predetermined temperature for a predetermined time; The initial MXene material is a MXene material containing -Cl, -Br or -I functional groups.

6. The method for preparing an electromagnetic shielding material according to claim 5, characterized in that: The preparation method further comprises a stripping step, wherein the A-MXene material having an accordion morphology obtained by the reaction is ultrasonically or mechanically stripped to obtain an A-MXene material having a two-dimensional structure; And / or, the compound of A includes: a hydride, an amide of A or a compound that can generate a single substance of A.

7. The method for preparing an electromagnetic shielding material according to claim 5 or 6, characterized in that: The preparation method of the initial MXene material comprises: etching component A in the MAX phase material by a molten salt method or a gas phase method; The molten salt method uses a halogen metal salt as an etchant; The gas phase method uses one or more of hydrogen halide gas, halogen element gas, and sublimated halogen metal salt gas as an etchant.

8. The method for preparing an electromagnetic shielding material according to claim 7, characterized in that: The molten salt method uses a chloride metal salt as an etchant.

9. The method for preparing an electromagnetic shielding material according to claim 5 or 6, characterized in that: The predetermined temperature is between 700° C. and 1200° C.; And / or, the predetermined time is between 0.01 min and 12 h.

10. The method for preparing an electromagnetic shielding material according to claim 9, characterized in that: The predetermined temperature is between 700 and 900°C.

11. The method for preparing an electromagnetic shielding material according to claim 9, characterized in that: The A is metal aluminum powder, and the reaction time is ≤5min; or, the A is metal silicon powder, and the reaction time is ≤4h; or, the A is metal gallium powder, and the reaction time is ≤5h; or, the A is metal germanium powder, and the reaction time is ≤5h; or, the A is metal indium powder, and the reaction time is ≤1h; or, the A is metal tin powder, and the reaction time is ≤4h; or, the A is metal zinc powder, and the reaction time is ≤2h.

12. An electromagnetic shielding film, characterized in that: The electromagnetic shielding film comprises the electromagnetic shielding material according to any one of claims 1 to 4; or, the electromagnetic shielding material obtained by the method for preparing the electromagnetic shielding material according to any one of claims 5 to 11.

13. A method for preparing an electromagnetic shielding film according to claim 12, characterized in that the steps include: The A-MXene material and a solvent are formulated into a dispersion, which is then sprayed, filtered or coated on a substrate to form a thin film layer.

14. An electromagnetic shielding coating, characterized in that: The coating contains the electromagnetic shielding material according to any one of claims 1 to 4; or, the electromagnetic shielding material obtained by the preparation method according to any one of claims 5 to 11.

Citation Information

Patent Citations

  • Methods and systems for preparing two-dimensional materials by vapor phase

    CN114620728B

  • Aluminum-based alloy containing nano Ti2AlN particles and preparation method thereof

    CN112267048A

  • Method for preparing MAX phase material through MXene conversion and application

    CN115367754A

Cited By

  • MXenePANi-based electrical response microwave reflectivity adjustable device and preparation method and application thereof

    CN121038259A